Perlindungan Hukum Terhadap Pernikahan Dibawah Tangan Dengan Wali Penghulu Berdasarkan Hukum Islam Yang Berlaku Di Indonesia (Studi Kasus Penetapan Pengadilan Agama Sukabumi Nomor: 0020/Pdt.P/2012/Pa.Smi.) - Ajang Nurjaman (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2018)
Marriage for Indonesian people is a phenomenon that is different from various aspects of life. Marriage can be used. Marriage can also be seen from various realities. Keywords: socio-cultural aspects, marriage. In addition, there are also activities mentioned between goods and services. One of the legal requirements of a marriage according to Islam is the existence of a marriage guardian. By these matters the problems referred to are as follows: (1) How is the marriage guardian regulated according to Islamic law in Indonesia? and (2) what legal action can be taken by a husband and wife who request that their marriage be refused because of their marriage guardian? The objectives of this thesis research are: (1) to find out how the marriage guardian is determined according to Islamic law in Indonesia, and (2) to find out what legal actions can be taken by the husband and wife whose application for marriage is dropped because of his marriage guardian The research methods used in this study are normative juridical research methods, using pragmatic truths where something is true if the truth can be proven. This research thesis uses primary legal material in the form of secondary data which is qualitative in nature which is a descriptive description of words and does not use numbers The results of this thesis research are: (1) the guardian of marriage according to the religion of Islamic law basically consists of: (a) guardian of the court, (b) the guardian of the judge. And (c) muhakkam guardian. Whereas in the customary regulations in Indonesia, the marriage guardian consists of: (a) the guardian of the court, and (b) the guardian of the judge. Thus the guardian of muhakkam which is recognized for its existence in Islamic law, at the meeting there are no rules in the wedding invitation rules in Indonesia, and (2) legal actions that must be carried out by a married couple who are not recognized by their marriage are: (a) remarriage , (b) seek legal appeal, or (c) make an effort to review.